Test “KROK-2” Tasks in GASTROENTEROLOGY - Доценко, Сергій Якович; Рекалов, Дмитро Геннадійович; Данюк, Інна Олександрівна (My University, 2019)
Test “KROK-2” Tasks in GASTROENTEROLOGY for independent preparation to practical studies for English-speaking students of medical faculty of 6 course. Practical work is represented as collection of test tasks and clinical tasks with standard of true answers in gastroenterology.
Keywords: гастроентерологія; тестові завдання